Two Novel Biomarker Candidates for Differentiating Basal Cell Carcinoma from Trichoblastoma; Asprosin and Meteorine Like Peptide - Kocaman, Nevin; Yuksel, Esma Inan; Demir, Betul; Calik, Ilknur; Cicek, Demet (Churchill Livingstone, 2022)
Introduction: BCC (Basal Cell Carcinoma) and trichoblastoma are skin tumors originating from the hair follicle. BCC is the most common non-melanoma skin cancer. Differential diagnosis of BCC from trichoblastoma, which is a common benign tumor in terms of histology, morphology, and immunohistochemistry, is not possible. The effects of adipokines on tumorigenesis have attracted attention. Materials and Methods: By examining the effects of Aspmsin and Meteorine like peptide (METRNL) on these tumors, it is aimed to reach new information in the differential diagnosis of BCC and trichoblastoma. Twenty normal healthy tissue, 17 basal cell carcinoma and 12 trichoblastoma samples were included in the study. Results: Increased expression of Aspmsin and METRNL was observed in tumor and stromal tissues in BCC. Although overexpression of METRNL was observed in the lesion area in trichoblastoma, no increase in Asprosin expression was observed. Asprosin and METRNL immunoreactivity were found to be statistically significantly higher in BCC samples compared to control and trichoblastoma. Conclusion: Asprosin and METRNL can be used in the diagnosis of BCC. METRNL can be used in the diagnosis of trichoblastoma. These biomarkers are helpful for differentiation between BCC and trichoblastoma.
Keywords: Basal Cell Carcinoma; Trichoblastom; Asprosin; Meteorine Like Peptide; Immunohistochemistry